Tinjauan Literatur: Integrasi Nilai Lokal dan Peran Pranata Sosial dalam Pendidikan di Madrasah - Rizqiani Nuraisyah; Mu’alimin Mu’alimin (Journal of Creative Student Research, 2024)
This article reviews various studies related to the application of local values in education based on social institutions, specifically in madrasahs and pesantren. It emphasizes how local value-based education, such as mutual cooperation and Islamic ethics, can shape students' character, strengthen social cohesion, and preserve local cultural identity. The literature discussed includes sociological and educational concepts related to social institutions as tools for cultural transformation in society. This finding highlights the importance of local value-based education in strengthening social identity, which serves not only as a medium for transferring knowledge but also as an agent of social change.